KAJIAN AKURASI DEM HASIL STEREOPLOTTING PADA FOTO UDARA FORMAT MEDIUM (STUDI KASUS : KAWASAN LEMBAH UNIVERSITAS GADJAH MADA) - , IDA MELASARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Technology for photogrammetric data processing, especially aerial photograph has evolved towards digital era. One of the products is DEM (Digital Elevation Model). DEM from aerial photo can be produced using computers and supporting software. It can be done by automatic stereoplotting or interactive stereoplotting. The purpose of this research is to know the DEM accuraccy obtained from interactive stereoplotting of medium format aerial photo through Relative Orientation stage. The location of research is Lembah Universitas Gadjah Mada area with varying tophography. Data needed to conduct this study were medium format aerial photo, DEM data resulted from LiDAR classification and data orthophoto. The stages in data processing are all orientation process (IO, RO and AO) for producing EOP value. Analysis of DEM accuracy was calculated by comparing the Z coordinate of sample points of DEM data resulted from interactive stereoplotting with DEM resulted from LiDAR data clasification. Than interactive stereoplotting process was executed to produce a DEM data. The accuracy level of DEM resulted from interactive stereoplotting can be determined by calculating the standard deviation of the sample data in the form of a sample points. The data samples were selected such that the chosen sample could represent the overall data population. The number of samples used in this research were 203 sample points. From the calculation, it was obtained that in the average height difference is 0.38 meter and the standard deviation is 0.43 meter. The higest height difference is 2.68 meters while the smallest height difference is 0 meters. Of the 203 sample data, there are 144 sample data have smaller height difference than the value of maximum accuracy. DEM accuracy was previsiously determined based on operator ability to do interactive stereoplotting on aerial photo.